Nasal juvenile angiofibroma: Current perspectives with emphasis on management. Issue 5 (15th February 2017) - López, Fernando; Triantafyllou, Asterios; Snyderman, Carl H.; Hunt, Jennifer L.; Suárez, Carlos; Lund, Valerie J.; Strojan, Primož; Saba, Nabil F.; Nixon, Iain J.; Devaney, Kenneth O.; Alobid, Isam; Bernal–Sprekelsen, Manuel; et al.
ABSTRACT: Juvenile angiofibroma is an uncommon, benign, locally aggressive vascular tumor. It is found almost exclusively in young men. Common presenting symptoms include nasal obstruction and epistaxis. More advanced tumors may present with facial swelling and visual or neurological disturbances. The evaluation of patients with juvenile angiofibroma relies on diagnostic imaging. Preoperative biopsy is not recommended. The mainstay of treatment is resection combined with preoperative embolization. Endoscopic surgery is the approach of choice in early stages, whereas, in advanced stages, open or endoscopic approaches are feasible in expert hands. Postoperative radiotherapy (RT) or stereotactic radiosurgery seem valuable in long‐term control of juvenile angiofibroma, particularly those that extend to anatomically critical areas unsuitable for complete resection. Chemotherapy and hormone therapy are ineffective. The purpose of the present review was to update current aspects of knowledge related to this rare and challenging disease. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1033–1045, 2017